On Optimal Wage Indexation - Karni, Edi (Journal of Political Economy, 1983)
The observed practice of contracting for labor services in advance introduces stickiness or friction into the economic system. In the presence of monetary and real stochastic disturbances the stability of the levels of employment and output hinges on the nature of the wage contracts. In this paper we demonstrate the existence of optimal indexation schemes that are capable of eliminating the aforementioned friction by duplicating the equilibrium that would obtain if labor services were contracted for after the stochastic disturbances were realized.